2016
DOI: 10.1007/s12016-016-8559-2
|View full text |Cite
|
Sign up to set email alerts
|

Atopy and Specific Cancer Sites: a Review of Epidemiological Studies

Abstract: Mounting evidence appears to link asthma and atopy to cancer susceptibility. This review presents and discusses published epidemiological studies on the association between site-specific cancers and atopy. PubMed was searched electronically for publications between 1995 and 2015, and cited references were researched manually. Quantitative studies relating to atopy, allergy, or asthma and cancer were identified and tabulated. Despite many exposure-related limitations, patterns in the studies were observed. Asth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 110 publications
(82 reference statements)
4
47
2
Order By: Relevance
“…Expression levels of HDC and H2R are positively associated with increased survival in colorectal cancer patients [ 68 ], and some epidemiological studies support the association of atopy with the reduced incidence of some cancers [ 69 , 70 ], reinforcing a possible role of histamine in blocking tumour development.…”
Section: Regulatory and Immunomodulatory Functions Of Histaminementioning
confidence: 99%
“…Expression levels of HDC and H2R are positively associated with increased survival in colorectal cancer patients [ 68 ], and some epidemiological studies support the association of atopy with the reduced incidence of some cancers [ 69 , 70 ], reinforcing a possible role of histamine in blocking tumour development.…”
Section: Regulatory and Immunomodulatory Functions Of Histaminementioning
confidence: 99%
“…To this end, several epidemiologic studies have observed history of asthma and/or allergies or higher serum IgE levels to be inversely associated with risk of various cancers (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). However, results have been inconsistent, and in fact, some research suggests that atopic disease may be associated with increased risk of cancer, potentially due to persistent immune stimulation (12,22,23).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiologic evidence documenting associations between allergic conditions and cancer has been mixed (16,17). The most consistent and robust inverse associations have been reported between all three allergic conditions and risk of brain cancer, with relative risks varying between 0.3 and 0.8 (17)(18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%